Heterotopic, not evolutionary and intrauterine ovarian pregnancy - Tang, Luis (2015)
A rare case of a spontaneous heterotopic pregnancy, intrauterine and ovarian, seen at Clinica Santa Isabel in Lima is presented. A 35-year-old patient was seen for menstrual delay, scanty vaginal bleeding and positive pregnancy test. Transvaginal ultrasound showed small gestational sac with absence of embryonic echoes. Uterine curettage was performed on 01/11/2006 obtaining chorial villi with non-molar hydropic degeneration at histologic examination. Ten days later, transvaginal ultrasound control was done because of persistent vaginal bleeding and abdominal pain, showing a left ovary mixed tumor with small inner echolucid image. An emergency laparotomy was performed; findings were 200 mL hemoperitoneum and an elongated, retrouterine, soft, purple mass dependent of left ovary, in relation to ectopic ovarian pregnancy.